Pelatihan Pengolahan Sampah Plastik Menggunakan Metode Ecobrick di Bank Sampah Mojokrapak Berseri Jombang - Sufaidah, Siti; Zainul Arifin, Muhyidin; Khafidhoh, Nur (Institut Teknologi dan Sains Mandala, 2024)
Plastic waste is non-degradable inorganic waste. The impact caused by plastic waste, namely the results of burning plastic waste are harmful compounds such as CO2, CO, NOX, and SOX which trigger birth defects in babies, to hormone dysfunction, and cancer. In order to reduce this impact, the Mojokrapak “beautiful” waste bank was established in Mojokrapak Village. Unfortunately, this goal has not been fulfilled by the Mojokrapak bank waste. The purpose of this activity is to provide training to the community and the management of the Mojokrapak Village waste bank to process plastic waste into valuable goods using the ecobrick method. The training activities will be held from July to August 2023 at the Mojokrapak Garbage Bank hall. The results of the training show that the community's understanding of the importance of processing waste into valuable goods has increased after the training. This can be seen from the enthusiasm of the community in training activities.